Efficacy of intralesional immunotherapy with Vitamin D3 injection in cutaneous warts: A clinical observational study - Geeta Sharma; Shilpi Sharma (Clinical Dermatology Review, 2023)
Background: Skin warts are benign tumors caused by infection of keratinocytes with human papillomavirus (HPV), visible as well-defined hyperkeratotic protrusions. Recently, immunotherapy is emerging as a new modality in the treatment of viral warts. Immunotherapy using Vitamin D3 is being tried widely for the treatment of warts. It is based on enhancing the immune system to achieve an HPV-targeted immune reaction. Objective: The objective of this study was to evaluate the safety and efficacy of intralesional Vitamin D3 for the treatment of viral warts. Materials and Methods: This was a hospital-based longitudinal study of 55 patients with viral warts. 0.5 ml Vitamin D3 solution (600,000 IU, 15 mg/ml) was injected in the base of the wart. A maximum of four warts per session were injected at 2-week intervals until resolution or for a maximum of four treatment sessions. The clinical assessment was done by pre- and posttreatment photographic comparison at baseline, before each treatment session, and after the completion of treatment. Results: Thirty-five patients (63.63%) showed complete clearance, 15 patients (27.27%) showed partial clearance, and 5 patients (9.09%) patients showed no improvement. No significant side effects were observed except for pain and mild swelling at the site of injection. Conclusion: Intralesional Vitamin D3 immunotherapy seemed to be an effective, safe, inexpensive treatment with minimal side effects.